STUDY OF GERMINATION REGARDING THE COMBAT OF WEEDS IN MEADOWS WITH REFERENCE TO CIRSIUM VULGARE SPECIES - Lisena Piscoran; Teodor Rusu (Agricultura)
The meadow is the land surface covered with grassy vegetation, made up mostly of perennial plants, belonging to different botanical families, the production of which is used for feeding animals, by grazing or mowing. Cirsium vulgare, the spear thistle, bull thistle or common thistle, is a species of the Asteraceae genus Cirsium, widespread throughout Europe, western Asia and northwestern Africa. It is also found in North America, Africa and Australia and is an invasive weed in some areas.